Linking metaphors of the future with socio-cultural prospects among Taiwanese high school students. (November 2016) - Chen, Kuo-Hua
Highlights: A sample of 854 Taiwanese high school students was surveyed. "The strawberry" generation's metaphors demonstrate capability of critical and self-reflective ways of thinking. Their preferred stories of the future involve from an open and global environment to a multicultural and sharing world. Young people have started to demonstrate the phenomenon of generational replacement. Abstract: This study is an investigation of diverse future metaphors used by Taiwanese high school students with the values and meanings that lie underneath them. The results show that "the strawberry" generation's chosen metaphors demonstrate their capability of critical and self-reflective ways of thinking. They also exhibit a deep sense of global awareness, foresight capacity and their role as a change agent for a better future. Their preferred stories of the future involve an open and global environment, broad and diversified friendship, leisure and travel over work, family and relationships, and most importantly, a multicultural and sharing world. The most crucial conclusion is that when young people are asked to discuss their future, they begin to explore new possibilities.